Designing 3-D Prints for Blind and Partially Sighted Audiences in Museums: Exploring the Needs of Those Living with Sight Loss. Issue 2 (2nd July 2020) - Wilson, Paul F.; Griffiths, Susan; Williams, Ellis; Smith, M. Paul; Williams, Mark A.
Abstract: Modern museum practice embraces equal access for all, but access for blind and partially-sighted (BPS) audience remains problematic given the ocularcentricity of museums. Many museum professionals and BPS visitors remain frustrated by the degree of accessibility on offer. The use of 3-D printed replicas as a handling surrogate represents a solution, allowing BPS visitors to engage tactually with museum content while minimizing risk. However, the design of such replicas is poorly researched. This exploratory examination of the design of 3-D printed replicas utilizes semi-structured interviews, sensory observations and content analysis to examine BPS perceptions of museum objects in the absence of interpretational support. Interpretation was dominantly multisensory, while participants found it easier to determine material traits than object traits, with textual, geometrical and optical properties being of use. Assistive approaches rather than major alterations were favored. Overall, museum professionals should consider how the process of 3-D printing influences BPS perception.